2018
DOI: 10.31014/aior.1992.01.01.9
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction: A Research Study of College Students in India

Abstract: The Journal of Economics and Business is an Open Access publication. It may be read, copied and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Further, the addiction is higher in those who are younger in age (Simkova and Cincera, 2004), especially among adolescent students (Siomos et al , 2008). Contrarily, Menon et al (2018) found that older students are more prone to internet addiction than younger students.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Further, the addiction is higher in those who are younger in age (Simkova and Cincera, 2004), especially among adolescent students (Siomos et al , 2008). Contrarily, Menon et al (2018) found that older students are more prone to internet addiction than younger students.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, with regards to gender, there were mixed results with some studies finding females to be more susceptible and indicating higher internet addiction levels than males (Heo et al , 2014; Simkova and Cincera, 2004). Others found that males exhibit higher degrees of internet addiction than females (Cecilia et al , 2013; Li et al , 2014; Menon et al , 2018; Zhang et al , 2008).…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The findings demonstrated the need for developing and implementing prevention programs for young students who are motivated and cognitive, practiceoriented, and reflexive, as well as a systematic strategy for their implementation in the framework of the educational space. Menon et al (2018) conducted a study on "Internet Addiction: A Research Study of College Students in India" to explore the extent of internet addiction in a management institute in India. In this study, 300 students (first, second and third-year students) from an Indian management institution were sampled to determine the prevalence of internet addiction.…”
Section: Literature Review On Internet Addictionmentioning
confidence: 99%
“…Some studies focus on the tactics and technologies used for identity protection (Balfe, 2014; Stewart, 2014) and are less significant from the point of view of legal researchers. There are studies showing reflections on the human psychology, intrapersonal characteristics of the offenders (Hadzhidimova & Payne, 2019) studying the causes and reasons behind the youths’/adolescents’ committing crimes, online internet addiction and the associated risk factors (Hahn & Kim, 2014; Henn, 2013; Menon et al, 2018). Most of the studies also focus on child pornography and sexual abuse, its varied dimensions, awareness and impact on individual, family and culture (Mitchell & Jones 2013; UNODC, 2015; Wolak et al, 2014), and the social and psychological impact of cyberattacks (Bada & Jason, 2020) and do significantly contribute towards the need for regulating the usage of online media.…”
Section: Aim and Objectivesmentioning
confidence: 99%